(untitled) - Deitel, Harvey M. (Upper Saddle River, N.J., 2001)
Gives students the knowledge to start their own e-businesses by teaching about the programming technologies for developing Web-based e-business and e-commerce solutions
Keywords: Internet programming,World Wide Web,Electronic commerce,Business enterprises,Hoạt động kinh doanh; Computer networks,Mạng máy tính